Developmental Change in Action Perception: Is Motor Experience the Cause?. (27th February 2018) - Loucks, Jeff; Sommerville, Jessica
Abstract : Human actions are complex stimuli containing several perceptual dimensions an observer could attend to. Research indicates that attention to the perceptual dimensions of action undergoes a process of perceptual narrowing between 4 and 10 months, during which infants' attention to configural and temporal information in action decreases over time, while attention to hand information is maintained. This research explored whether infants' active experience with grasping is related to perceptual narrowing in action. Across two studies, we tested 6‐month‐old infants' attention to changes in these action dimensions and also assessed their grasping ability. Infants who were more proficient at grasping showed a pattern more consistent with perceptual narrowing (decreasing attention to configural and temporal information) relative to those less proficient at grasping, especially for attention to configural information. In addition, attention to hand information appears to undergo U ‐shaped development between 4 and 10 months, as 6‐month‐olds did not recover attention to the hand change. These findings add to a growing body of research showing that infants' motor experience broadly influences their perception of others' action and may follow a complex developmental pathway that diverges from perceptual narrowing over the first year.